Synapsin-dependent reserveo pool of synaptic vesicles supports replenishment of the readily releasable pool under intense synaptic transmission - Vasileva, Mariya; Horstmann, Heinz; Kuner, Thomas (European journal of neuroscience, 2012)
Synapsins are abundant synaptic vesicle (SV)-associated proteins thought to mediate synaptic vesicle mobility and clustering at most synapses. We used synapsin triple knock-out (TKO) mice to examine the morphological and functional consequences of deleting all synapsin isoforms at the calyx of Held, a giant glutamatergic synapse located in the auditory brain stem. Quantitative three-dimensional (3D) immunohistochemistry of entire calyces showed lower amounts of the synaptic vesicle protein vGluT1 while the level of the active zone marker bassoon was unchanged in TKO terminals. Examination of brain lysates by ELISA revealed a strong reduction in abundance of several synaptic vesicle proteins, while proteins of the active zone cytomatrix or postsynaptic density were unaffected. Serial section scanning electron microscopy of large 3D-reconstructed segments confirmed a decrease in the number of SVs to approximately 50% in TKO calyces. Short-term depression tested at stimulus frequencies ranging from 10 to 300 Hz was accelerated only at frequencies above 100 Hz and the time course of recovery from depression was slowed in calyces lacking synapsins. These results reveal that in wild-type synapses, the synapsin-dependent reserve pool contributes to the replenishment of the readily releasable pool (RRP), although accounting only for a small fraction of the SVs that enter the RRP. In conclusion, our results suggest that synapsins may be required for normal synaptic vesicle biogenesis, trafficking and immobilization of synaptic vesicles, yet they are not essential for sustained high-frequency synaptic transmission at the calyx terminal.